Perception du processus d’apprentissage du français par les lycéens de la classe XI de SMA Negeri 2 Demak - Anindyah Setianingsih; Diah Vitri Widayanti (Universitas Negeri Semarang, 2025)
The learning process in the classroom is the core of all academic activities. The role of the teacher in the learning process provides experience to students. The experience gained by students affects students’ perceptions of the French learning process. This study aims to describe students’ perceptions of the French learning process in class XI at SMA Negeri 2 Demak, both in terms of perceptions of each teacher activity and individual student perceptions. The method in this research uses quantitative descriptive method. Respondents in this study were 11th grade students of SMA Negeri 2 Demak. Data collection using in this study is a questionnaire and documentation. The questionnaire in this study used bivariate correlation validity and to measure reliability using the Alpha formula. Data analysis using percentage descriptive analysis. The results showed that the average value of student perceptions was 69.56 and the average value of the learning process showed 56.81. These results indicate that student perceptions of the learning process show a good category.